Digital subtraction radiography for monitoring dental demineralization - Eberhard, Jörg; Hartman, B.; Lenhard, Markus; Mayer, Thomas; Kocher, Thomas; Eickholz, Peter (Caries research, 2000)
The aim of the present study was to evaluate the assessment of progression of demineralization by digital subtraction radiography. In each of 14 extracted human teeth, 2 approximal enamel demineralization lesions were induced in vitro to simulate dental caries. A modified tunnel preparation with glass ionomer fillings was performed on one lesion of every tooth as a model of caries inhibition. Every week, radiographs were obtained under standardized conditions over a period of 42 days. The radiographs were digitized and calibrated for grayscales. Reference landmarks were chosen and aligned for the different pictures by computer-assisted imaging to adjust the images for projective distortions. The images of the 7th, 14th, 21st, 28th, 35th and 42nd day were subtracted from the baseline radiograph. The mean value of gray values of the subtraction images was calculated and ANOVA tests for repeated measurements and paired t tests were used for statistical analysis. The results of the present study indicate that statistically significant gray level changes due to progression of demineralization could be detected in the radiographic images by subtraction analysis. Differences between glass ionomer-filled and nonfilled lesions failed to reach significance. The introduced method may have the potential to detect and document minute caries progression.
Gesehen am 09.02.2021